2021
DOI: 10.13189/ujer.2021.090113
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of EFL Teachers towards Using Smartphones in the Classroom during COVID-19 Pandemic

Abstract: Literature on smartphone technology indicates that smartphones nowadays are almost accessible to everyone with a high percentage even in the least developing countries like Palestine. This accessibility might be due to the various applications, functions and features of the new generations of the smartphones. Hence, the current study aimed to investigate the attitudes of EFL teachers towards using smartphones in the classroom among Palestinian secondary students during COVID-19 pandemic. The study also aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
(54 reference statements)
1
5
0
Order By: Relevance
“…This finding is also supported by other research which indicates zero correlation, meaning that there is no correlation between teachers' gender in the use of mobile devices (Papadakis, 2018;Subawa et al, 2021). Similarly, a study intended to probe the attitudes of English First Language (EFL) teachers towards the use of smartphones in the classroom among Palestinian secondary school students showed that there were no statistically significant differences in their teaching practice between the teachers' use of technology owing to gender (Dweikat & Hasan, 2021) The findings in the present study showed that there are no statistically significant differences found between teachers' perceptions towards acceptance of tablets in the classroom, and their age. This finding is reinforced by the study undertaken by Foutsitzi and Caridakis (2021) to explore Greek high school teachers' perceptions in the teaching of philology with the use of ICTs as part of their teaching practice.…”
Section: Discussionsupporting
confidence: 67%
“…This finding is also supported by other research which indicates zero correlation, meaning that there is no correlation between teachers' gender in the use of mobile devices (Papadakis, 2018;Subawa et al, 2021). Similarly, a study intended to probe the attitudes of English First Language (EFL) teachers towards the use of smartphones in the classroom among Palestinian secondary school students showed that there were no statistically significant differences in their teaching practice between the teachers' use of technology owing to gender (Dweikat & Hasan, 2021) The findings in the present study showed that there are no statistically significant differences found between teachers' perceptions towards acceptance of tablets in the classroom, and their age. This finding is reinforced by the study undertaken by Foutsitzi and Caridakis (2021) to explore Greek high school teachers' perceptions in the teaching of philology with the use of ICTs as part of their teaching practice.…”
Section: Discussionsupporting
confidence: 67%
“…In this research, the smartphone became the most apparatus used by students to listening English through video. Based on Dweikat and Hasan (2021), the use of smartphones offers a positive attitude for teaching and learning. The majority of English department and non-English department expressed the entertainment like song and daily activities topic were suitable for improving listening skill.…”
Section: Discussionmentioning
confidence: 99%
“…Several textbook evaluation studies conducted in the Saudi Arabian context employed a Likert scale checklist to evaluate the weaknesses and strengths of specific English textbooks (Alamri, 2008;Alenezi, 2019;Al-Hajailan, 1999;Alhamlan, 2013;AlHarbi, 2017;Alharbi, 2015;Aljouei & Alsuhaibani, 2018;Almalki, 2014;Al-Sowat, 2012). This type of research into L2 textbook evaluation continues to be performed in multiple L2 contexts around the globe (Ahour, Towhidiyan, & Saeidi, 2014;Dweikat, 2011;Jahangard, 2007;Hammad, 2014;Hanifa, 2018;Henriques, 2009;Zohrabi, Sabouri, & Behroozian, 2012).…”
Section: Evaluation Of L2 Textbooks From a Macro Perspectivementioning
confidence: 99%
“…The importance of English language textbooks as a major component of the educational system in many countries has resulted in an extensive body of research on textbook evaluation (Abraha, 2007;Ahour, Towhidiyan, & Saeidi, 2014;Al-Alyani, 2017;Alamri, 2008;Albedaiwi, 2014;Alenezi, 2019;Al-Hajailan, 1999;Alhamlan, 2013;Al-Harbi, 2017;Alharbi, 2015;Aljouei & Alsuhaibani, 2018;Allehyani, Burnapp, & Wilson, 2017;Almalki, 2014;Alshumaimeri & Alzyadi, 2015;Al-Sowat, 2012;Dweikat, 2011;Jahangard, 2007;Hammad, 2014;Hanifa, 2018;Henriques, 2009;Madjdi & Rokhayani, 2018;Nguyet & Van Long, 2020;Tok, 2010;Zohrabi, Sabouri & Behroozian, 2012;Omari, 2018;Kalfut, 2020;Kalfut, 2021). However, to date, few studies have thoroughly examined the research methods used to evaluate L2 textbooks.…”
mentioning
confidence: 99%